Front Cover: Optimization of N‐Piperidinyl‐Benzimidazolone Derivatives as Potent and Selective Inhibitors of 8‐Oxo‐Guanine DNA Glycosylase 1 (ChemMedChem 1/2023). (19th January 2023) - Wallner, Olov; Cázares‐Körner, Armando; Scaletti, Emma Rose; Masuyer, Geoffrey; Bekkhus, Tove; Visnes, Torkild; Mamonov, Kirill; Ortis, Florian; Lundbäck, Thomas; Volkova, Maria; Koolmeister, Tobias; Wiita, Elisée; et al.
Abstract : The Front Cover shows a group of three enzyme copies of the human 8‐oxo Guanine DNA glycosylase 1 (OGG1) safeguarded by specific and potent inhibitors TH8535 and TH5487. In that way oxidative DNA damage in form of 8‐oxo Guanine is accumulated and leads to further oxidation products and base mispairing—threatening genome stability in high oxidative stress cancers. The article describes the discovery of TH5487 as the most frequently used molecular probe of OGG1 and TH8535 as the most potent member of the class. Cover Art design by Florian Ortis and Njomza Isufaj. More information can be found in the Research Article by Olov Wallner, Armando Cázares‐Körner, Maurice Michel et al.